Characterization of cadmium biosorption by inactive biomass of two cadmium-tolerant endophytic bacteria Microbacterium sp. D2-2 and Bacillus sp. C9-3 - Long, Jianyou (Ecotoxicology (London, England), 2021)
© 2021. The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.